Understanding and quantifying perturbations in a complex networked supply chain - Leong, Yu Rong (2016)
The first part of this final year project examined how the heat transfer concepts of heat conduction, heat convection and heat radiation can be adapted to describe the material, financial and information flow within a supply chain. A linear supply chain was first used to explore how a 1-D heat conduction model can be utilized to describe the flow of material goods within a supply chain, which is then extrapolated to cover a complex networked supply chain using the 2-D heat conduction model. Similarly, a conceptual analogy was conceived to describe both the financial and information flows using convection and radiation concepts respectively. However, verification of the model still remains to be conducted to determine its validity. The second part of this final year project investigated the performance and behavior of an eScentz production line through the creation of a simulation model, the objective being to identify regions of bottlenecks and propose solutions to mitigate such bottlenecks, as well as to investigate the propagation of disruptive impacts in the form of machine breakdowns. From the simulation runs, it was discovered that Parylene Coating was the bottleneck process given its long processing time, resulting in a Work-In-Process (WIP) inventory of 2625. The recommended solution was deemed to be outsourcing the manufacturing of parts to an external company, reducing WIP inventory by 60% without requiring significant capital investment. Thereafter, the impact of a breakdown in the Parylene Coating machine was examined and similarly, it was discovered that while the purchase of an additional Parylene Coating was able to reduce WIP inventory by 88.8%, outsourcing of parts proved to be a more fiscally sensible solution.